Surface Science Tools for Nanomaterials Characterization - Kumar, Challa S.S.R (Springer, 2015)
Fourth volume of a 40volume series on nano science and nanotechnology, edited by the renowned scientist Challa S.S.R. Kumar. This handbook gives a comprehensive overview about Surface Science Tools for Nanomaterials Characterization. Modern applications and state-of-the-art techniques are covered and make this volume an essential reading for research scientists in academia and industry.